Sustainable and green decomposition of cyanotoxins and cyanobacteria through the development of new photocatalytic materials - Choi, Hyeok; Han, Changseok; Antoniou, Maria G. (My University, 2021)
Photocatalytic oxidation for the degradation of cyanobacteria (aka blue–green algae) and cyanotoxins has been extensively studied since its first application by Robertson and Lawton in 1997. Along with testing treatability of various cyanobacteria and cyanotoxins, significant advances in materials engineering have been made. Improvements on the properties of titanium dioxide and other inorganic photocatalysts include bandgap narrowing, adsorption-mediated decomposition, electron–hole recombination prevention, photocatalyst immobilization, reactor design innovation, light emitting diode usage, and/or oxidant injection, resulting in more green, sustainable, and scalable photocatalytic oxidation processes. Herein, we report not only synthesis methods, materials properties and performance, and features of photocatalysts but also transformation products, and toxicity evaluation of treatments. Studies have delivered significant scientific findings and described promising features such as visible light activation, floating photocatalytic reactors, photocatalytic membranes, and multiple functionality for insitu remediation under solar radiation, ultimately. At last, scale-up potential of the materials and reactors and future research needs are discussed.
Keywords: Microcystins; Cyanoginosin LR; Cyanobacterial Toxins